PENGARUH ARTIBUT PRODUK DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN PRODUK SUNSCREEN GLAD2GLOW DI KOTA SURABAYA - Pratama, Ovitia Rerolia Fitria; Wardhani, Nuruni Ika Kusuma (Unitri Press, 2024)
The younger generation in Indonesia is now becoming more concerned with the health of the skin, so the use of sunscreen is increasing. When someone decides to buy sunscreen, things like how good the product is and how much they trust a brand is crucial. The aim of this research is to see how Product Attributes and Brand Trust influence the Purchase Decision of Glad2Glow Sunscreen Products in Surabaya City. The sampling approach was targeted with a total of 90 survey respondents. This research method is a quantitative method with the Partial Least Square method. (PLS). The results of this study show that Product Attributes have a positive influence on Purchase Decisions, and Brand Trust has a positive effect on Purchasing Decision.